365 Battlefield to farm field: risk perceptions of US military veterans transitioning into agriculture. (1st September 2016) - Bendixsen, Casper G; Barnes, Kathrine; Weichelt, Bryan; VanWormer, Jeff; Keifer, Matthew C
Abstract : Background: Prompted by wars in the past two decades largely in the Middle East, the United States veteran population in the United States often struggles with unemployment. America is increasingly occupied by the mental health ramifications of deployment. Domestically, the United States grapples with securing a healthy and abundant food source to support a large food insecure population in the midst of decreases in the number of farms and increasing food imports. The veteran-to-farmer (V2F) movement converges within these two concerns to provide jobs and potential therapeutic benefits to veterans through food production. Methods: The project combines a grounded theory approach with epidemiology to understand a broad range of implications for the V2F movement. Grounded theory will be utilised to conduct semi-structured interviews and participant-observation to explore veteran's safety behaviours and construct an understanding of how knowledge, attitudes, and beliefs about safety result in health or injury. Veteran's health and safety outcomes will be measured using existing US Veterans Affairs' mental and emotional health analysis tools. Results: Outputs will include modified quality of life and reintegration assessment instruments specific to V2F. This project will also explore if the unique experiences and training of veterans creates a worldview that puts them at particular risk and so establishes V2Fs as a new vulnerable worker population. Results pending and will be available by September, 2016. Conclusions: The study offers a new and emergent means to implementing research into practice by deriving hypotheses from a grounded theory approach and testing them through traditional epidemiological methods. While the V2F movement continues to expand, the unique risks posed to veterans through agriculture should be explored, recognised, and prevented for veterans as an at-risk population.